Remote sensing of natural phenomena - Regodić, Miodrag D.; Benić, Željana Ž. (Vojnotehnički glasnik / Military Technical Courier, 2013)
There has always been a need to directly perceive and study the events whose extent is beyond people’s possibilities. In order to get new data and to make observations and studying much more objective in comparison with past syntheses - a new method of examination called remote sensing has been adopted. The paper deals with the principles and elements of remote sensing, as well as with the basic aspects of using remote research in examining meteorological (weather) parameters and the conditions of the atmosphere. The usage of satellite images is possible in all phases of the global and systematic research of different natural phenomena when airplane and satellite images of different characteristics are used and their analysis and interpretation is carried out by viewing and computer added procedures. Introduction Remote sensing of the Earth enables observing and studying global and local events that occur on it. Satellite images are nowadays used in geology, agriculture, forestry, geodesy, meteorology, spatial and urbanism planning, designing of infrastructure and other objects, protection from natural and technological catastrophes, etc. It it possible to use satellite images in all phases of global and systematic research of different natural phenomena. Basics of remote sensing Remote sensing is a method of the acquisition and interpretation of information about remote objects without making a physical contact with them. The term Daljinska detekcija is a literal translation of the English term Remote Sensing. In French it isTeledetection, in German - Fernerkundung, in Russian - дистанционие иследования. We also use terms such as: remote survailance, remote research, teledetection, remote methods, and distance research. The basic elements included in Remote Sensing are: object, electromagnetic energy, sensor, platform, image, analysis, interpretation and the information (data, fact). Usage of satellite remote research in monitoring natural phenomena The images taken from Remote Sensing have helped men to use the environment and natural resources in a better way. It is expected that the developement of new technologies will spread the usage of satellite images for the welfare of mankind as well. Besides monitoring the surface of the Earth, the satellite monitoring of the processes inside the Earth itself is of great importance since these processes can cause different catastrophes such as earthquakes, volcano eruptions, floods, etc. Usage of satellite images in monitoring atmospheric phenomena The launch of artificial earth satellites has opened new possibilities for monitoring and studying atmospheric phenomena. A large number of meteorological satellites have been launched by now (Nimbus, Meteor, SNS, ESSA, Meteosat, Terra, etc.). Since these images are primarily used for weather forecast, meteorologists use them to get information about the characteristics of clouds related to their temperature, the temperature of the cloud layer, the degree of cloudness, the profiles of humidity content, the wind parameters, etc. Meteosat satellites Meteosat is the first European geostationary satellite designed for meteorological research. The use of these satellites enabled the surveying in the visible and the near IR part of the spectrum as well as in the infrared thermal and water steam track. Based on these images, it was possible to obtain data such as: height of clouds, cloud spreading and moving, sea surface temperature, speed of wind, distribution of the water steam, balance of radiation, etc. Usage of satellite images in monitoring floods Satellite images are an excellent background and an initial phase for preventing severe catastrophic events caused by floods. Due to satellite images, it is possible to manage overflown regions before, during and after floods. This enables prevention, forecasting, detection and elimination of consequences, i.e. demage. Satellite images are of great help after the withdrawal of water, for the estimation of damage and flood recovery. Usage of satellite images in detectingearthquakes Remote sensing is widely used in the procedure of detecting and locating earthquakes. Earthquakes can be detected by the combination of geophysical methods with multispectral and radar images. By combining these nethods, we can monitor the conditions of seizmic areas. The obtained information can be computed and sent to information centres in stationary stations where the modelling of earthquake-affected terrains is carried out. Usage of satellite images in monitoring volcanos Remote sensing has been used ifor examining a large number of active vulcanos. Monitoring is performed several times, during and after eruptions. The modelling of volcanic areas enables the definition of lava-effusion zones,and potentially dangerous zones, which is further used for planning the protection of affected areas. Usage of satellite images in monitoring fire (blaze) One of important methods of investigating, forecasting and monitoring forest fires is remote sensing. Satellite images are valuable in discovering fires and in mapping affected areas within the geographical-information system (GIS), as well as in the estimation of demage caused by fire. Satellite images can also be usedto estimate the temperature on the Earth surface. Conclusion Remote sensing becomes an increasingly important and unavoidable method of the acquisition of data on geospacein general. The importance of thus obtained data is invaluable in all phases of monitoring catastrophic events, from detecting their onsets through monitoring their spreading and effects to the phase of recovery. New generations of sensors enable systematic monitoring, recording and measuring different data important for detecting changes and processes in the sea, on the ground and in the atmosphere. The procedures of remote sensing enable surveying (recording) and registration of different natural phenomena. Thus acquired data can reveal ongoing activities in these environments and, moreover, predict posssible catastrophic scenarios in the nature..